Tari Baris Babuang pada Upacara Pegingsiran Jro Pingit di Desa Pengotan - Hartawan, I Wayan; Dhana, I Nyoman; Sama, I Nyoman (Humanis; Vol 25 No 1 (2021)DO - 10.24843/JH.2021.v25.i01.p14, 2021)
Bali is one of the islands that is very well known to foreign countries. Besides being famous for its natural beauty it is also known by the nickname of the Thousand Temples. It is known that the Balinese are usually inseparable from the sacred arts which are believed to complement the ceremony. Meanwhile in the village of Pengotan has a sacred dance that is the Baris Babuang dance. Baris Babuang is one element of universal culture that is part of the arts. Baris Babuang dance is danced by carrying banana fronds which can also be called the papah biu war. This research focuses on two things, namely the Babuang Baris Dance Function at the Pegingsiran Jro Pingit ceremony in Pengotan Village and the Meaning of the Babuang Baris Dance at the Pegingsiran Jro Pingit ceremony in Pengotan Village. The purpose and objective of this research is to find out the function and meaning of the implementation of the Babuang Baris Dance at the Jro Pingit ceremony. Then the authors use the Functional Theory of B. Malinowski and the ceremonial theory of William Robertson Smith to help strip the results of the research. This study uses qualitative methods to describe an event or phenomenon that occurs in a research subject such as behavior, perception, motivational action holistically and analyzed by collecting data that has previously been recorded besides audio visual recording, then recorded again in the recapitulation sheet then processed in the form of scientific writing. The results of this study state that, the function of Babuang Row Dance in relation to public trust, functions as a reinforcement of solidarity between citizens and the meaning of Babuang Row Dance to invoke safety, the meaning of kinship meaning the symbol of harmonization.